Penggunaan Aplikasi Geogebra Dalam Pembelajaran Matematika Untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Kelas XI-1 SMA Negeri 5 Medan - Rekha Indah Sitanggang; Rika Kartika; Susanna Ronaria Harahap (Departement of Mathematics Education, 2024)
The use of information technology is currently very developed, especially in the world of education. Various technologies can be used as mathematics learning media. One of the learning media that supports mathematics learning is the Geogebra application. Geogebra is a computer program that can be used to visualize mathematical concepts. This research aims to measure students' mathematical critical thinking abilities with the help of Geogebra in class Classroom Action Research (PTK). The research method used was PTK with two cycles, each consisting of two meetings. Each cycle is carried out with a focus on learning models and critical thinking skills in mathematics. The research results showed that there was a significant increase in learning outcomes in the second cycle compared to the first cycle. The first cycle succeeded in increasing students' learning preparation, interest and attitudes towards lessons, as well as students' learning activities through the Teaching at The Right Level (TaRL) approach. In the second cycle, improvement efforts were made by integrating the Geogebra application and the Culturally Responsive Teaching (CRT) approach, which resulted in consistent improvements in all aspects of observation